2001
DOI: 10.1074/jbc.m105669200
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of a p53-related Protein Kinase Expressed in Interleukin-2-activated Cytotoxic T-cells, Epithelial Tumor Cell Lines, and the Testes

Abstract: A human protein kinase, p53-related protein kinase (PRPK), was cloned from an interleukin-2-activated cytotoxic T-cell subtraction library. PRPK appears to be a homologue of a growth-related yeast serine/threonine protein kinase, YGR262c. However, a complementation assay using YGR262c-disrupted yeast indicated that PRPK is not functionally identical to the yeast enzyme. PRPK expression was observed in interleukin-2-activated cytotoxic T-cells, some human epithelial tumor cell lines, and the testes. The intrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 25 publications
3
74
1
1
Order By: Relevance
“…However, we found that the kinase domain of PAN2, like that of PAN1, is catalytically inactive in vitro, consistent with the absence of several residues in the kinase domain that are typically required for catalytic activity. While we cannot rule out the possibility that there are some conditions in vitro or in vivo in which PAN2 is catalytically active as shown for other proteins with atypical kinase domains (Abe et al, 2001;Min et al, 2004), PAN2 is inactive in vitro under a wide variety of conditions tested. Approximately 10% of all kinases in both plant and animal genomes and almost 20% of Arabidopsis RLKs are predicted to lack catalytic activity based on their sequences (Manning et al, 2002;Castells and Casacuberta, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that the kinase domain of PAN2, like that of PAN1, is catalytically inactive in vitro, consistent with the absence of several residues in the kinase domain that are typically required for catalytic activity. While we cannot rule out the possibility that there are some conditions in vitro or in vivo in which PAN2 is catalytically active as shown for other proteins with atypical kinase domains (Abe et al, 2001;Min et al, 2004), PAN2 is inactive in vitro under a wide variety of conditions tested. Approximately 10% of all kinases in both plant and animal genomes and almost 20% of Arabidopsis RLKs are predicted to lack catalytic activity based on their sequences (Manning et al, 2002;Castells and Casacuberta, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, in every case analyzed, the deficiency of these enzymes strongly impairs cellular growth and proliferation. Interestingly, the possibility that fast growing or proliferating cells could have special requirements for t 6 A-modified tRNAs is further hinted by the fact that human PRPK was originally identified in a transcriptional screen performed in IL-2-activated lymphocytes (52). In Drosophila, tcs3 is differentially expressed in different anatomical structures and developmental times (53).…”
Section: Discussionmentioning
confidence: 99%
“…This result directly linked PRPK activity with p53 stabilization (Abe et al, 2001;Facchin et al, 2003). PRPK expression is detected in epithelial tumor cell lines, as well as in normal testis, showing a mild increase in G1 phase (Abe et al, 2001).…”
Section: Introductionmentioning
confidence: 96%
“…In addition, recent studies have identified the influence of TOR on bulk endocytosis, as well as its reciprocal relation in the control of cell growth and autophagy (Hennig et al, 2006). Yeast pID261/Bud32 is an atypical Ser/Thr kinase conserved throughout metazoans and required for normal cell growth and survival (Abe et al, 2001;Facchin et al, 2002b;Facchin et al, 2002a). Studies in S. cerevisiae have uncovered two fundamental roles for Bud32: as a constituent of the KEOPS complex (kinase, putative endopeptidase and other proteins of small size), a regulator of telomere structure (Downey et al, 2006); and as a part of the EKC (endopeptidase-like kinase chromatin-associated) transcription complex (Kisseleva-Romanova et al, 2006).…”
Section: Introductionmentioning
confidence: 99%